Assessing the impact of phasing out battery cages and switching to colony cages in the poultry industry of New Zealand : a thesis report submitted to Massey University in fulfilment of the requirement for obtaining Master Degree in Agri-Commerce - Mayaba, Harold (Massey University, 2019)
This research aims to assess the impact of phasing out battery cages on New Zealand’s poultry farming. In 2012, the New Code of Welfare for layer hens came with a recommendation to phase out battery cages in favor of colony cages as an alternative production system. A 10-year phasing out period was offered for a smooth transition to the new system such that it will be illegal to raise hens in battery cages after 2022. However, seven years into this transition period, about 44.7 percent of eggs are still being produced under the battery cage system in New Zealand, suggesting high compliance cost on farmers. Other production systems used by egg producers include; barn, colony and free-range system. A review of the literature offered some general leads into the demerits and merits of alternative production systems, their impacts on the welfare of hens, and the cost of production. In order to assess the impact of phasing out of battery cages in the New Zealand context, a survey was conducted on the poultry farmers to establish how they have been affected by the New Code of Welfare. The survey was complemented by follow-up face-to-face interviews or telephone calls to these participants. Besides descriptive data analysis, preliminary regressions were conducted on selected variables. Secondary data were combined with survey data to obtain these results. A better understanding of the impact of phasing out battery cages that this research offers is important as farmers are making decisions on the best production methods to use in this new environment.
Keywords: barn; battery cages; colony cages; free-range; poultry; 300208 Farm management, rural management and agribusiness